“The new extreme right” - Nilsson Per-Erik (Nordicom Review)
Contemporary France is a prolific arena for post-fascist actors, parties, and movements. Self-proclaimed alternative news outlets and publishing houses serve as forums for information and mobilisation, through various strategies, to resist an alleged onslaught by the enemies of the nation and its people: multiculturalism, feminism, political correctness, political corruption, and civilisational decay. In this article, I explore uncivility as a discursive logic within the French post-fascist media-ecology, focusing on the conspicuous use of irony and discursive displacement. More specifically, I discuss how sardonic irony as an uncivil discursive strategy is employed to navigate the legal boundaries of free speech and how discursive displacement, coupled with irony, is used as an affective identificatory technique in post-fascist discourse.